Introduction of a Novel Figure of Merit for the Assessment of Transparent Conductive Electrodes in Photovoltaics: Exact and Approximate Form. Issue 26 (1st June 2021) - Anand, Aman; Islam, Md Moidul; Meitzner, Rico; Schubert, Ulrich S.; Hoppe, Harald
Abstract: Transparent conductive electrodes (TCEs) are key components of photovoltaic devices. Being transparent, they allow light to enter the device, and being conductive, they allow the photocurrent generated to be drawn into the outer electric circuit. Ideally, TCEs exhibit maximum light transmission and conductivity at the same time. However, both properties have to be balanced. Depending on the photovoltaic material system, the selection of the most suitable TCE is crucial and is assessed by so‐called figures‐of‐merit (FOM). Here, a novel and exact FOM that explicitly considers the impact on photovoltaic performance is proposed. This novel FOM exhibits several useful attributes, among them: i) proportionality to the potential power output of the photovoltaic device, ii) normalization with regard to the theoretically ultimately attainable photovoltaic performance and, thus, it provides above all iii) meaningful guidance for the development of advanced TCEs. Based on the exact FOM, the transition sheet resistance is defined as the parameter, which separates the so‐far unidentified two regimes of TCE operation: transmittance versus conductance limited. An overview of realized state‐of‐the‐art semitransparent electrodes is reassessed and compared herein. Furthermore, the TCE requirements for various photovoltaic material systems are assessed in dependence on the spectral range of their operation. Abstract : A novel figure of merit (FOM) for assessing transparent conductive electrodes for photovoltaics is proposed. This FOM is linear to the attainable photovoltaic power, normalized with regard to the Shockley–Queisser limit, dimensionless and, thus, overall directly meaningful. The approximate form of this FOM distinguishes between the transmittance and conductance limited regimes, via the definition of a transition sheet resistance.